Chinua Achebe’s Worldview As Reflected in Some of His Selected Works - Eruaga, Abigail Obiageli; Okeke, Ethel Ngozi (NIU Journal of Social Sciences, 2021)
The worldview, ideology, vision, belief and ethics of most writers are overtly or covertly reflected in their works. Chinualumogu Achebe is a writer whose belief in the humane function of art is not in doubt. Through his essays, interviews, speeches, novels and writings in general, he unequivocally demonstrates that art, a product of society, is for the service, benefit, deliverance and redemption of man and society. This redemptive vision of art manifests in all his writings. Achebe abhors racism, oppression, prejudice, marginalisation and subjugation of any group of the society just as he contracts relationships with people and fellow writers that are racially-liberated, broad-minded, just and humanely inclined irrespective of clime, creed and colour. This paper is a reflection on Achebe’s moral vision of art as enunciated in his selected speeches and works. It argues that Achebe perceives art as a unifying, humanising, refining and redemptive agent of man and society, and concludes that Acbebe has no doubt, attained a status of immortality through his art. Keywords : Worldview, moral vision, humane function, art, Achebe, redemption, man, society.